Problems of the Structural Approach: Methodology and Approach - Alanbar, Omar (Dirasat: Human and Social Sciences, 2022)
This research aims to investigate some of the problems of the Structural Approach which has a huge impact on various schools of Arabic literary criticism as a result of the scientific shift it introduced to the field. This paper sheds light on some of the most consequential complications of the Structural Approach which are frequently cited as points of criticism. The objective of considering such issues is to offer the Arab literary critic with ways to deal with and overcome some of the most substantial challenges of the Structural Approach. This work can be classified as falling under the umbrella of reviewing the Structural Approach of literary criticism.